A Unified Constitutional View of Financial Punishment: Synthesizing the Excessive Fines Clause and Bearden-Based Protections - Feinzig, Joshua M. (2020)
This Note coordinates the Eighth Amendment Excessive Fines Clause with the Fourteenth Amendment wealth-discrimination protection set forth in Bearden v. Georgia. It is generally assumed that the two protections operate independently: while the Excessive Fines Clause protects individuals against exorbitant financial obligations, Bearden limits the state from converting criminal debt into a severe liberty deprivation. But in recognizing how the two doctrines are normatively and functionally reinforcing, this Note proposes a single framework for considering financial punishment’s constitutionality. If the Eighth Amendment protection applies at the imposition of a financial punishment, Bearden provides a “second look” at the constitutionality of that punishment. Or, put another way, the Eighth Amendment is a preemptive look at the downstream poverty-based liberty deprivations that Bearden secures individuals against. Appreciating this relationship affords additional authority to both protections, and suggests a number of improvements to existing safeguards